2020
DOI: 10.1024/0300-9831/a000684
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin B12 in treating recurrent aphthous stomatitis: A review

Abstract: Abstract. Vitamin B12, a water-soluble vitamin, plays a vital role in the formation of hematopoietic stem cells and has been associated with oral mucosal diseases, mainly recurrent aphthous stomatitis (RAS). The latter is a debilitating condition, and B12 was proposed as a potential treatment given its role in regenerating oral mucosal tissue. There is conflicting evidence that B12 deficiency causes RAS. Five of the seven randomized controlled trials reviewed used the inactive form of B12 (cyanocobalamin) as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Water-soluble vitamin B12 has been linked to oral mucosal illnesses, including recurrent aphthous stomatitis (RAS), and is essential for the development of hematopoietic stem cells [21]. Some RAS patients have been shown to have deficiencies in zinc, hematinics (iron, vitamin B12, and folic acid), and vitamin D. However, the causes of how hematinic deficits could affect how the immune response develops in RAS have not been sufficiently clarified [22].…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble vitamin B12 has been linked to oral mucosal illnesses, including recurrent aphthous stomatitis (RAS), and is essential for the development of hematopoietic stem cells [21]. Some RAS patients have been shown to have deficiencies in zinc, hematinics (iron, vitamin B12, and folic acid), and vitamin D. However, the causes of how hematinic deficits could affect how the immune response develops in RAS have not been sufficiently clarified [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies noted that a lack of micronutrients (e.g., vitamins, serum iron, ferritin, and folic acid) may affect the occurrence and development of RAS, but this result is controversial [11][12][13][14]. Some studies Evidence-Based Complementary and Alternative Medicine showed that vitamin B12 treatment was effective in patients suffering from RAS [13,15]. A Turkish study on serum zinc and vitamin D reported an association between zinc deficiency and RAS [16].…”
Section: Discussionmentioning
confidence: 99%
“…The administration routes are various, including oral, sublingual, intramuscular (IM), intranasal, intravenous, and deep subcutaneous formulations, with parenteral administration usually reserved for severe cases of deficiency in practice. However, a Cochrane review in 2018 concluded that low-quality evidence suggests oral and IM vitamin B12 have similar effects regarding normalizing serum vitamin B12 levels, with an advantage for oral treatment being less expensive (Taleb, 2020).…”
Section: Treatment Of Cutaneous Manifestationsmentioning
confidence: 99%
“…Vitamin B12, also known as cobalamin, is a water-soluble vitamin that is essentially found in food of animal source. It has an important role in hematopoietic cell formation (Brescoll, 2015;Taleb, 2020). Vitamin B12 is present in different forms in the human body, with methylcobalamin and adenosylcobalamin being the two metabolically active forms (Brescoll, 2015).…”
Section: Introductionmentioning
confidence: 99%